농축수산물 브랜드 육성정책 개선방안 - 최병옥 (한국농촌경제연구원, 2009)
This study is aimed to improve the brand supporting systems for agricultural, livestock and marine products, in the hope of boosting efficiency of the national relevant systems. Here, to this end, the concept of agricultural, livestock and marine products brands is defined, the current status and problems in it are pointed out for examination and evaluation of the systems, and several improvements in the policies are suggested. Recently the agricultural, livestock and marine products markets are facing rapid environmental changes, so it is urgent to establish and operate market differentiation policies. In particular, with active discussions on trade liberalization for agricultural, livestock and marine products with other countries, the growing imports of agricultural, livestock and marine products have come to conflict with domestic agricultural, livestock and marine products. The changes in domestic agricultural, livestock and marine products markets and the food consumption structures require competitive domestic products and differentiation strategies. In terms of these, diverse sectors, including the government, local governments, and producers’ organizations, are trying to build brands to differentiate national products. Although the current brand policies for agricultural, livestock and marine products are a part of systematization process, they were named brand-building/supporting projects, generating a lot of controversy. Also, some producers and consumers are confused between trademarks and brands, causing a brand explosion. The agricultural trademarks numbered 6,552 in late 2006, which were more of trademarks than brands. The number of livestock brands is 647 in late 2008, and the number of marine products brands has yet to be set. Today, the rice brands supporting system is trying to grow producers in the size based on systematization and support uniform quality of rice, attempting at production of quality rice. Fruit trees brands, based on mid and long-term development strategies, require systematic brand-building, while horticulture and vegetable farming brands aim at enhancing brand competitiveness through innovations in production/distribution facing with changes in market environment. The livestock and marine products brands, also, are trying to stabilize sales networks by enlarging the sizes and expanding markets, and activate relevant promotions and advertisements. However, since problems are mounting in each sector, hampering those supports or limiting the brand management, it is required to modify the systems as a whole. Now, the agricultural brand building projects are implemented in a unsystematic structure, and diverse businesses, such as agricultural distribution systematization project, agricultural distribution enlargement project, agricultural brands building projects and so on, are mixed together, which should be systematically rearranged. Also, agricultural distribution should be modified, and divided into harmonization of farms, agricultural brand building, and evaluation. As PB brands are rapidly growing among large retailers, countermeasures to this tendency should be considered, too. First of all, in order to foster agricultural distribution, the substructures should be organized based on strong unity. It is also needed to benchmark foreign cases to establish our own systematic methods for all processes from production to distribution and marketing. Once, through these efforts, competitive organizations are built, it is advisable to move on to brand building processes, in order to foster brand firms with high competitiveness at home and abroad. In addition, professionalism and management of agricultural distribution should be enhanced, and brand firms should be managed and evaluated continuously after designation. It is also necessary to combine and adjust relevant governmental funds for agricultural distribution, to systematically grow agricultural distribution organizations and set supporting systems dedicated to stronger capability.
Keywords: 농산물마케팅; 브랜드